Assessment of Environmental Health and Safety Status of Public and Private Schools in Shiraz City in Educational Year of 2014 - Rabieh Hoseini; Abooalfazl Azhdarpoor (Shiraz University of Medical Sciences, 2016)
Background: The environmental health of schools is included all activities that have a direct effect on preservation of student's health and the prevention of the diseases' transmission and promotion of the level of the environmental health of schools. Objectives: This cross-sectional study was conducted to evaluate the environmental health and safety status of public and private schools of Shiraz city, Iran, in 2014. Materials and Methods: The total number of schools was included 1055 public schools and 490 private schools. The multistage random stratification sampling was performed and samples of 752 schools were met. In order to collect data, a list based on form of regulation of school environmental health was used and 74 questions were selected and the data were analyzed using the SPSS software version 19. Results: The results showed that there was no proper health buffet in 43% of the public schools and 65% of the private schools. Also, only 17% of total schools had a hygiene educator. In terms of availability to equipment and tools, 90% of the public schools and 96% of the private schools had proper conditions. In terms of security and safety, 71% of the public schools and 73% of the private schools had proper conditions. Conclusions: With regard to these findings, it can be concluded that the separately investigation of environmental health status and security of schools at all four areas is necessary.